Panoramic view of the migration phenomenon and measures to address this problem - Zárate Palomino, Helaman Jahairo (2023)
Migration is a multidimensional phenomenon that, historically, has developed since the emergence of humanity, due to the movements of human groups for different causes or purposes. Nowadays, migratory flows stem from different economic, political and social aspects that are immersed in globalization; for example, capital mobility, job search, ethnic or religious differences, armed conflicts or poverty. These factors have become radicalized over the years to the point where the living conditions of people displaced voluntarily or involuntarily have been violated. Given this environment, spaces for dialogue have been consolidated at a global level and the presence of States such as Peru to evaluate the migration crisis, and reach agreements that allow the establishment of a regulatory framework on this matter at the international and national levels, respectively. Due to what has been expressed in previous lines, it is relevant to analyze the current situation of the migration phenomenon, as well as the decisions and measures adopted at a global level in order to regulate and reduce human displacements. Likewise, among the main conclusions it was found that migratory flows progressively increase due to different circumstances; and because of this, countries like Peru and international organizations instill dialogue and cooperation to reduce the impact of this fact.